A new scale insect host family (Hemiptera: Asterolecaniidae) for Aphytis (Hymenoptera: Aphelinidae) in China. Issue 15 (26th April 2019) - Wang, Zhu Hong; Ge, Jun Qing; Zhang, Hui; Zhang, Zhengli; Si, Yu; Huang, Jian; Polaszek, Andrew
ABSTRACT: Aphytis wasps are among the most important natural enemies of scale insects, and armoured scale insects (Hemiptera: Diaspididae) have generally been considered as the only hosts of the genus Aphytis . Host records from non-diaspidids have been considered erroneous by most authors. A new scale insect host, Bambusaspis notabilis (Russell), however, belonging to Asterolecaniidae (Hemiptera), has been found as the host of a new Aphytis species in our field investigations. Aphytis bambusaspis Wang, Huang & Polaszek sp. nov. is described and illustrated, and detailed photographs of the key characters of the female and male of the new species are provided. Type specimens are deposited in Fujian Agriculture and Forestry University, Fuzhou, Fujian Province, China and Natural History Museum, London, UK. Previously published host records of Asterolecaniidae are reviewed. http://www.zoobank.org/urn:lsid:zoobank.org:pub:0BE6DB64-CB75-466A-B974-8A620FAFEA1E